Remnants of Native Vegetation Surrounding Do Not Affect the Diversity and Density of Birds in Brazilian Grassland-Restoration Sites - Silva, Thaiane Weinert da; Fontana, Carla Suertegaray (Frontiers in Ecology and Evolution, 2021)
Since in general the surrounding landscape influences the species diversity and abundance in fragments of native vegetation, an amount of native-vegetation cover nearby may also positively affect communities in restored areas, regardless of the sizes of individual habitat patches. We investigated for the first time whether the species richness, total abundance, and density of grassland birds in restoration sites are influenced by the amount of native grassland in the surrounding landscape in the Brazilian Pampa. We sampled birds by point counts in five restoration sites in the most representative area of grasslands in Brazil. We established an outer buffer zone with a 1 km-radius around the point-count areas in each site, and calculated the percentage of native grassland vegetation in the surrounding landscape. Bird species richness and abundance did not show a significant response to the amount of neighboring native grassland in restored areas. Individual analyses of the density of seven bird species associated to grassland also showed similar pattern. We believe the vegetation structure in these restoration sites may already been sufficiently re-established to provide necessary resources and a suitable habitat for the birds. Even so, we assume that previously existing landscape features were important for recovery of the vegetation structure, as continuous native grassland in the surroundings. Thus, we recommend consider the landscape context as an additional issue in studies dealing with conservation strategies for recovery of grasslands in Brazil.